1982
DOI: 10.1037/h0090966
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward disabled persons as a function of social context and specific disability.

Abstract: The main purpose of this study was to test a hypothesis that situational context affects attitudes toward disabled persons. A total of 191 nondisabled adult subjects completed the Disability Social Relationship Scale, a newly devel oped instrument that includes social situation subscal es of Work, Dating, and Marriage, and disability subscal es of Amputee, Epilepsy, Cerebral Palsy, and Blind. As hypothesized, the results yielded significant differences across social situations and among specific disabilities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
54
3
3

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 12 publications
7
54
3
3
Order By: Relevance
“…The training should not only be a knowledge-based type of training, but also a practice-based training where students can apply their knowledge about disability and interact with other students with disabilities to bridge the gaps between these groups. Realistically, attitudes toward disability should be measured on the basis of social context and specific disability (Grand et al, 1982). When the attitudes toward people with disabilities are measured in a situational context, the outcome will provide a meaningful and practical interpretation on exploring individuals' attitudes toward people with disabilities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The training should not only be a knowledge-based type of training, but also a practice-based training where students can apply their knowledge about disability and interact with other students with disabilities to bridge the gaps between these groups. Realistically, attitudes toward disability should be measured on the basis of social context and specific disability (Grand et al, 1982). When the attitudes toward people with disabilities are measured in a situational context, the outcome will provide a meaningful and practical interpretation on exploring individuals' attitudes toward people with disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…The reactions towards people with disabilities in the social context vary in the literature. Antonak (1981) and Grand, Bernier, and Strohmer (1982) found that interactions between people with disabilities and people without disabilities often result in shorter conversations, less physi-cal contact, and less personal and meaningful conversations (as cited in Miller et al, 2009, p. 211). Negative attitudes were particularly more apparent in the context of dating and marriage.…”
Section: Social Distance Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…While it does not detract from the richness of our data set, we are acutely conscious of the fact that norms and attitudes are notoriously tricky to measure. First, responses to questions on attitudes are inexorably ascribed by context -who the respondent is, where they live, how they were raised, among others (see for instance Grand, Bernier and Strohmer, 1982). These can affect both the respondents' interpretation of the question as well as their response.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Physical attractiveness (i.e., appearance) is a poor indicator of health levels, potentials for achievement, and success when applied to the aged or persons with a handicap. Grand, Bernier, and Strohmer (1982) investigated attitudes toward disabled persons as a function of social situation and specific disability. They found that (according to the nondisabled raters) the less visible the disability, the more likely the person was acceptable for association within various social contexts.…”
mentioning
confidence: 99%